Socio-Cultural Dynamics of the Subak System: A Comparative Study of the Impact of Regional Development in Kabupaten Buleleng - Rifka Pasaribu; I Putu Sriartha; I Gede Astra Wesnawa (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2026)
This research aims to analyze the impact of regional development on socio-cultural changes in the Subak system in Buleleng Regency. The research uses a descriptive qualitative approach with a comparative case study design at two locations, namely Subak Sekumpul (representing a low development area) and Subak Banyumala (representing a high development area). Data were collected through in-depth interviews, observations, and documentation, which were then analyzed based on the three aspects of the Tri Hita Karana (THK) philosophy: parahyangan, pawongan, and palemahan. The research results show that the intensity of socio-cultural changes is uneven across each aspect. The aspect of Palemahan is experiencing high-intensity changes, characterized by the massive conversion of rice fields into residential or plantation areas, a decrease in irrigation water flow, and an increase in the use of modern agricultural technology. The pawongan aspect shows a moderate intensity of change, evident from the shift in social relationship patterns from the traditional gotong royong system to a wage-based work system, as well as the decreasing participation of members in subak meetings. Meanwhile, the parahyangan aspect has a low intensity of change because religious values and the performance of main rituals are still maintained as the sacred foundation of community life, although the involvement of the younger generation is starting to decrease. Overall, regional development encourages a shift in societal orientation from collective-religious values to more economic-individualistic ones. This process of change occurs gradually, starting from the physical aspect of the environment (pabelasan), which then influences the social aspect (pawongan) and religious activities (parahyangan). In conclusion, strategic efforts are needed to maintain a balance between modernization and the preservation of cultural values so that the Subak system remains sustainable amidst rapid regional development.